Influência do ZrO2 nas propriedades eletrocrômicas do filme de V2O5 - Loi, Monique da Rocha (2016)
The motivation and importance of this project is the search of alternatives in order to optimize the energetic expenses and consequently minimize the ambient impact and reduced the cost. With this, one solution that was studied is the used of thin film with electrochromic properties and their applications in smart windows. This project propose a systematic study of vanadium oxide films and vanadium oxide films doped with zirconium oxide. Then, it was done preparation and characterized electrochemically in order to be use as counter electrode in an electrochromic devices. The method used was the Sol Gel process, using isopropoxide of zirconium Zr(OCH2CH2CH3 ) 4 ] and oxytripropoxide of vanadium V[OV(OC3H7 ) 3 ] as precursors and isopropyl alcohol as solvent and acetic acid as catalyzer. The deposition of the films were realized by dip-coating technique on substrate FTO. After the deposition the films has been submitted a heat treatment at 350°C during 30 minutes in ar atmosphere. These film been characterized by different electrochemical technique, such as cyclic voltammetry and chronoamperometry. In order to study the morphology the films Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) was realized. Also was study the structure of the film by X-ray diffraction. The optical properties of the films UV-Vis spectroscopy was done. With all characterization the V 2O5 and V 2O5 :Zr been studied is theses film can be used as counter electrode in an electrochromic device.